1995
DOI: 10.1002/mc.2940130205
|View full text |Cite
|
Sign up to set email alerts
|

N‐methylnitrosourea—lnduced Ki‐ras codon 12 mutations: Early events in mouse thymic lymphomas

Abstract: N-Methylnitrosourea (NMU)-induced codon 12 Ki-ras mutations were analyzed in premalignant thymic lymphomas from C57BL/6J mice by using a selective polymerase chain reaction amplification strategy. The frequency of codon 12 Ki-ras mutations was 67% (16 of 24) in NMU-treated animals with premalignant stage I disease. Previously, animals with different stages of disease had been analyzed for cytogenetic changes and for mutations in the p53 tumor suppressor gene. The genetic changes observed were early-activating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Ki-rus mutations are found in N-nitroso-bis(2-oxopropyl)amin+induced hyperplasia of the pancreas in hamsters [23] and in aberrant crypt foci and adenomas during azoxymethane-induced colon carcinogenesis in rats [24]. Ki-rus mutation also appears in the early stage of N-methylnitrosoureainduced thymic lymphoma [25]. Furthermore, some studies have shown that mutations in rus family genes occur before the appearance of histopathological changes.…”
Section: Discussionmentioning
confidence: 98%
“…Ki-rus mutations are found in N-nitroso-bis(2-oxopropyl)amin+induced hyperplasia of the pancreas in hamsters [23] and in aberrant crypt foci and adenomas during azoxymethane-induced colon carcinogenesis in rats [24]. Ki-rus mutation also appears in the early stage of N-methylnitrosoureainduced thymic lymphoma [25]. Furthermore, some studies have shown that mutations in rus family genes occur before the appearance of histopathological changes.…”
Section: Discussionmentioning
confidence: 98%
“…O 6 -methylguanine, induced in DNA by MNU treatment, gave rise to GC to AT transition mutations via mispairing with thymine during DNA replication (Cooke et al 2003, Engelbergs et al 2000. A number of studies on alkyl nitrosourea induced rodent tumors have shown that methylating N-nitroso carcinogens almost exclusively induced GC to AT transitions in the genes analyzed (Calvert et al 1996, Guzman et al 1992, Newcomb et al 1995, Ohgaki et al 1992, Sukumar et al 1983, Sukumar and Barbacid 1990, You et al 1989, Zaidi et al 1995, Zarbl et al 1985.…”
Section: Chemical Properties Of Nitroso Compoundsmentioning
confidence: 99%
“…Furthermore, O 6 MeG has been implicated in the MNU-induced transformation of ras proto-oncogenes (Jacoby et al ., 1992; Mariyama et al ., 1989; Newcomb et al ., 1995; Sukumar, 1989) and in cancer initiation (Becker et al ., 1996; Bos, 1989). O 6 MeG is efficiently repaired by O 6 MeG-DNA methyltransferase (MGMT) in a suicide reaction that inactivates MGMT (Kaina et al ., 2007).…”
mentioning
confidence: 99%